Cooperation Between Public Organizations in the Implementation of Spatial Data Infrastructures (SDI)s: A Case Study from Sweden - Olsson, Olov (Nordic Journal of Surveying and Real Estate Research, 2023)
Questions concerning cooperation are particularly relevant in complex projects where people from many organizations are involved and work together. There is a need to study and evaluate how better knowledge about cooperation can improve and make future projects more efficient. This case study is part of a research project aiming at evaluating the importance of abilities related to cooperation in the implementation of Spatial Data Infrastructure (SDI) projects. The problem at hand is that, many complex projects engage key personnel on different levels with limited experience on how to deal with questions of cooperation – both in planning and practical work. The aim of the study is to evaluate problems in cooperation using established theories and knowledge on cooperation, as well as to analyse whether problems of cooperation related to implementation specifically were a bottleneck in the studied project. Data capture is mainly based on open ended interviews. The study utilizes a framework including theories of cooperation and a model “talk – decision – action” (Brunsson, 2006). The results pointed towards problems in especially the action category. There was a lack of reciprocity between the cooperating parties, a lack of awareness about the need of daily cooperative behaviour in implementation activities and a potential risk of a free-rider problem. The most important lesson from the study is that, cooperation is a crucial component in a project of this kind, and that needed cooperation in practical implementation activities should be paid a lot of attention also in early planning activities.